Effect of ultrasonic vibration-assisted milling on surface quality of carbon fiber reinforced polymer - Yukun Zhang; Junxue Ren; Jinhua Zhou (Journal of Materials Research and Technology)
This paper studies the effect and mechanisms of ultrasonic vibration-assisted machining on the surface quality of carbon fiber reinforced polymer (CFRP), based on the kinematic characteristics of ultrasonic vibration-assisted milling. First, the kinematics of ultrasonic vibration assisted machining (UVAM) is analyzed, and cutting experiments are conducted to compare the surface roughness and surface damage of CFRP machined by UVAM and conventional machining under different spindle speeds. Furthermore, the influence of ultrasonic vibration on the tool rake angle and its surface smoothing effect are analyzed to discuss the mechanism by which ultrasonic vibration affects surface quality. The results show that using two different tools in ultrasonic vibration-assisted CFRP machining, the surface roughness was reduced by up to 9.9 % and 11.9 %, respectively. In addition, it was found that improper machining parameters may lead to increased damage. This study indicates that ultrasonic vibration can help improve the surface quality of CFRP milling under appropriate parameters and shows a certain potential for engineering applications.